(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of depression and identify associated factors among final-year high school students in Hanoi. Subjects and methods: A cross-sectional descriptive study on 986 grade 12 high school students in Hanoi from December 1, 2023 to May 30, 2024. Results: A total of 51.9% of students exhibited depressive symptoms at varying severity levels: 29.9% had minimal symptoms, 10.7% mild, 6.4% moderate, and 4.9% severe. Factors that were statistically significantly associated with depression included: gender, academic pressure, emotional bullying, cyberbullying, and smartphone addiction (p < 0.01). Among these, academic pressure, emotional bullying, cyberbullying, and smartphone addiction were associated with notably high odds ratios between affected and unaffected groups. Conclusion: A total of 51.9% of final-year high school students in Hanoi experienced depression at varying levels. Intervention strategies should focus on key associated factors, including academic pressure, emotional bullying, cyberbullying, and smartphone addiction among students.